Comparative analysis of efficacy and tolerability of tramadol versus diclofenac in treatment of knee osteoarthritis - Kanjiya, Rima; Kotadia, Ravi (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Present study was conducted on patients of osteoarthritis (OA) treated with the traditional drug diclofenac sodium and compares it with tramadol, with the primary objective for determining effectiveness and tolerability based on WOMAC scores. Methods: The study was conducted as a randomized clinical study of the effectiveness and tolerability of tramadol versus diclofenac in the treatment of knee OA, at Tertiary care institute of Gujarat in the department of orthopedics. Consecutive patients were allotted serially in two groups; tramadol group (n=75) One tablet orally twice daily for 8 weeks. Diclofenac group (n75) patients received 75 mg oral dose of diclofenac 2 times daily for a period of 8 weeks. Overall improvement was evaluated through various parameters. Results: About 33% decrease in the scoring of stiffness domain of the WOMAC OA index questionnaire in the tramadol group and a 21% decline in the diclofenac group was observed. There was a 65% decrease in the scoring of knee joint tenderness questionnaire in the tramadol group and a 44% reduction in the diclofenac group. Tramadol was found to be more effective in improving the WOMAC OA index. WOMAC score (overall) and knee joint tenderness scores were also improved by tramadol than diclofenac. Conclusions: There was a significant improvement in the standard of life in patients suffering from knee OA when treated with tramadol. Tolerability was better with tramadol than diclofenac.